Experimental Study on Acoustic Emission Characteristics of Granite and Sandstone under Uniaxial Compression - Yongshuai Sun; Fei Yu; Jianguo Lv (Geofluids)
In order to better apply acoustic emission technology to engineering practice, this paper carried out indoor acoustic emission test, and uniaxial compression tests of granite and sandstone under monotonic loading and grading loading were carried out and monitored. The influencing factors of the acoustic emission characteristics of the two rock samples were discussed and the characteristics of the acoustic emission signals corresponding to different stages of rock failure were analyzed. The analysis of the test results includes the curve fitting relationship between the AE event count rate, energy rate, and stress time and the changes of AE event count rate and energy rate under different loading methods. The results of the study are as follows: there is a quiet zone in the acoustic emission event before the rock is destroyed and destabilized, and the higher the rock strength, the more obvious the quiet zone; this important feature can be used as a precursor feature of rock mass failure for prediction, and the rock acoustic emission energy rate is more obvious in the quiet area before destruction than the acoustic emission event rate; rock acoustic emission has experienced initial compaction zone, rising zone, peak zone, and descending zone, whether different rocks go through each stage and how long each stage lasts is related to the nature of the rock; under different loading methods, the failure mechanism of rock is different; the different loading rates of monotonic loading and grading loading will affect the change rate of acoustic emission.